2021
DOI: 10.3390/insects12111005
|View full text |Cite
|
Sign up to set email alerts
|

The First Eight Mitogenomes of Leaf-Mining Dactylispa Beetles (Coleoptera: Chrysomelidae: Cassidinae) Shed New Light on Subgenus Relationships

Abstract: The taxonomic classification of Dactylispa, a large genus of leaf-mining beetles, is problematic because it is currently based on morphology alone. Here, the first eight mitochondrial genomes of Dactylispa species, which were used to construct the first molecular phylogenies of this genus, are reported. The lengths of the eight mitogenomes range from 17,189 bp to 20,363 bp. All of the mitochondrial genomes include 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), 2 ribosomal RNA genes (rRNAs), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…This phenomenon suggested that different selection pressures have been exerted on various functional genes in the mitochondria of Scolytinae during the evolutionary process. Comparable patterns of mitochondrial gene evolution have also been reported in several insect clades, including Psilidae (Diptera; Zhou and Yang, 2022), Cicadellidae (Hemiptera;Xu et al, 2020), Tortricidae (Lepidoptera; Huang et al, 2023), and Chrysomelidae (Coleoptera; Zhang et al, 2021), this suggests that the evolutionary pattern of mitochondrial genes may be relatively conserved among insects.…”
Section: Evolutionary Rate Nucleotide Diversity and Heterogeneity Amo...mentioning
confidence: 71%
See 1 more Smart Citation
“…This phenomenon suggested that different selection pressures have been exerted on various functional genes in the mitochondria of Scolytinae during the evolutionary process. Comparable patterns of mitochondrial gene evolution have also been reported in several insect clades, including Psilidae (Diptera; Zhou and Yang, 2022), Cicadellidae (Hemiptera;Xu et al, 2020), Tortricidae (Lepidoptera; Huang et al, 2023), and Chrysomelidae (Coleoptera; Zhang et al, 2021), this suggests that the evolutionary pattern of mitochondrial genes may be relatively conserved among insects.…”
Section: Evolutionary Rate Nucleotide Diversity and Heterogeneity Amo...mentioning
confidence: 71%
“…The largest noncoding region in these mitogenomes of Scolytinae beetles as well as most insects is usually located between 12S rRNA and trnI. It might be identified as the putative control region according to the conserved region aligned with other Coleoptera mitogenomes (Zhang et al, 2021). The length of the control regions of the four mitogenomes vary widely, ranging from 681 bp in E. similis to 1,004 bp in Xylosandrus sp.…”
Section: Protein-coding Genes and Codon Usagementioning
confidence: 99%
“…Intergenic spacers (IGSs) are non-coding regions typically found in metazoan mitochondrial genomes [14]. For example, in some species of beetle, known mitogenomes contain the IGS commonly found at the junction of the trnS2 (UCN) and nad1 genes [8,[15][16][17][18][19][20]. The IGSs have also been found between different genes in the mitogenomes of other beetles, such as between trnW and trnC [8], nad2, and trnW [21], trnI and trnQ [4,22,23], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common DNA barcoding genes used in animals is the mitochondrial cytochrome c oxidase subunit I (COI, cox1 ) (Hebert et al 2003a, b, Ratnasingham & Hebert 2007). The use of COI gene sequences has been widely employed as ‘barcodes’ for multiple invertebrate taxa (Du et al 2021, Meregalli et al 2021, Young et al 2021, Zhang et al 2021, Macher et al 2021) and previous studies have proved the high effectiveness of COI sequences as an identification tool for a great number of species of beetles (Raupach et al 2010, Bergsten et al 2012, Pentinsaari et al 2014b, Zhang et al 2019). The Barcode of Life Data System (BOLD) is an online platform that assemblage molecular, morphological, and distributional data and storages over 11 million records of COI sequences for all eukaryotic life (https://www.boldsystems.org/) (Ratnasingham & Hebert 2007).…”
Section: Introductionmentioning
confidence: 99%